2009
DOI: 10.1016/j.cell.2009.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin-1 and -2 Dosage Regulates Pressure Sensing

Abstract: Autosomal-dominant polycystic kidney disease, the most frequent monogenic cause of kidney failure, is induced by mutations in the PKD1 or PKD2 genes, encoding polycystins TRPP1 and TRPP2, respectively. Polycystins are proposed to form a flow-sensitive ion channel complex in the primary cilium of both epithelial and endothelial cells. However, how polycystins contribute to cellular mechanosensitivity remains obscure. Here, we show that TRPP2 inhibits stretch-activated ion channels (SACs). This specific effect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
286
5
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 303 publications
(299 citation statements)
references
References 47 publications
7
286
5
1
Order By: Relevance
“…Electrophysiology. Electrophysiological procedure has been previously described elsewhere [24,32]. Renal mechanotransduction R. Peyronnet et al scientific report…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiology. Electrophysiological procedure has been previously described elsewhere [24,32]. Renal mechanotransduction R. Peyronnet et al scientific report…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that Pkd1 gene disruption in vascular SMCs results in a reduced myogenic tone. 18 Functional roles for the polycystins in mechanosensation have been proposed in ECs as well as SMCs. In ECs, the proteins are involved in fluid shear stress sensing, thereby regulating calcium signaling and nitric oxide release.…”
mentioning
confidence: 99%
“…In mice with reduced Pkd1 expression in SMCs, stretch-activated channel (SAC) activity was decreased and the threshold pressure for myogenic contraction was significantly shifted to higher pressure values. 18 The ratio of polycystin-1/polycystin-2 regulates SACs activity, as polycystin-2 inhibits channel opening, whereas polycystin-1 reverses this inhibition. 18 It is likely that alterations in intracellular Ca 2 þ homeostasis contribute to the vascular phenotype in PKD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En réponse au flux d'urine, la flexion du cil déclencherait une augmentation transitoire du calcium intracellulaire, provenant du réticulum endoplasmique et du compartiment extracellulaire ; cette réponse requiert l'intégrité du cil, au moins dans les cellules en culture [31,32]. Ce rôle de senseur de la pression du flux dépend du taux respectif des protéines PC1 et PC2 [4,5,33]. Ainsi, chez les souris Pkd1 -/-, le cil des cellules des tubules proximaux se forme normalement, mais la réponse calcique qu'il induit est défectueuse [34].…”
Section: Nphp1-9unclassified